SYSTEM INVENTORY INFORMATION ON THE CV.AW ELEKTRIC KOTABUMI - Fevi Hamijaya; Novan Andriyanto (Jurnal informasi dan komputer, 2014)
ABSTRACTInformation System inventory on the CV.AW ELEKTRIC is the system that used in the warehouse of CV.AW ELEKTRIC Kotabumi the inventory data processing where data prosessing is still using the notes, like using a manual notes that use ledgers book and card stock. Therefore, many problems in the record, such as the accuracy of the information obtained is less detailed and tend to the information obtained is very slow. Therefore, the researchers are taking this matter to be investigated and created a better system. This is expected to help CV.AW ELEKTRIC to processing data inventory in the warehouse, so the information is relative more quickly and accurately.Development method of information system inventory are made by using waterfall method with using a system development tool flowchart document ( Flow map ), Context Diagram ( Context Diagram ), DFD ( Data flow Diagram ), table relationships, normalization from using programming language Visual Basic 6.0Information System Inventory on the CV.AW ELEKTRIC has the advantage program look attractive and easy to operate. This system as also capable of providing managerial assistance to the parties to determine whether inventory has been sold or still exist in the barn, and this system can help the user to control the stock of goods that can anticipate empty stocks and also easier to determine the amount of the order and the distance of time ordering the goods to the supplier.